Choosing health: qualitative evidence from the experiences of personal health budget holders. (October 2013) - Davidson, Jacqueline; Baxter, Kate; Glendinning, Caroline; Irvine, Annie
Objectives: Personal health budgets were piloted in the English National Health Service between 2009 and 2012. Semi-structured interviews with a sub-sample of early budget holders aimed to explore their experiences of receiving and using a budget. Method: Over 2000 people from 20 pilot sites were recruited to a multi-method evaluation of the personal health budget pilots. A sub-sample of 58 people was selected for qualitative interviews three months after the offer of a budget; 52 were re-interviewed six months later. The purposively selected sample reflected a range of health conditions, locality, age and gender. Results: Personal health budgets were reported to have positive impacts on health, health care and relatives/family. Benefits often extended beyond the condition for which the budget had been awarded. However, interviewees rarely knew the level of their budget; some reported difficulty in agreeing acceptable uses for their budget; and delays could occur in procuring chosen services or equipment. Conclusion: Patients' experiences offer valuable insights for the roll-out of personal health budgets beyond the pilot phase. Flexibility in how budgets are used may allow maximum benefits to be derived. Clear information about what budgets can and cannot be used for, with suggestions offered, will be useful. People with newly diagnosed or recent sudden onset conditions may need more help to plan their support, but all budget holders are likely to benefit from regular contact with staff for reassurance and continued motivation.